2007
DOI: 10.1002/cne.21379
|View full text |Cite
|
Sign up to set email alerts
|

Retinal ganglion cell dendrites undergo a visual activity‐dependent redistribution after eye opening

Abstract: Recent studies showed that light stimulation is required for the maturational segregation of retinal ganglion cell (RGC) synaptic connectivity with ON and OFF bipolar cells in mammalian retina. However, it is not clear to what extent light stimulation regulates the maturation of RGC dendritic ramification and synaptic connections. The present work quantitatively analyzed the dendritic ramification patterns of different morphological subtypes of RGCs of developing mouse retinas and demonstrated that RGCs in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(102 citation statements)
references
References 48 publications
(120 reference statements)
6
94
1
1
Order By: Relevance
“…We observed immunolabeling similar to that previously observed in the mouse retina using the same antibody (Quraishi et al, 2007;Xu and Tian, 2007;Puthussery et al, 2010;Hilgen et al, 2011).…”
Section: Anti-calretininsupporting
confidence: 86%
“…We observed immunolabeling similar to that previously observed in the mouse retina using the same antibody (Quraishi et al, 2007;Xu and Tian, 2007;Puthussery et al, 2010;Hilgen et al, 2011).…”
Section: Anti-calretininsupporting
confidence: 86%
“…A recent study combined the two-photon calcium imaging with the serial-section electron microscopy and suggested about 10% DSGCs in the mouse retina (Briggman et al 2011). One group of ON-OFF DSGCs labeled by 1,1=-dioctadecyl-3,3,3=,3=-tetramethylindocarbocyanine perchlorate (DiI) is counted for 16% of total RGCs (Sun et al 2002), while another study suggested 21% (Xu and Tian 2007). Huberman and colleagues (2009) suggested the total ON-OFF DSGCs is about 20 -36%.…”
Section: Discussionmentioning
confidence: 99%
“…3C and Table 1), which falls into the range in the above study. ON DSGCs are counted for 5% of the total RGCs in the rabbit retina (Oyster 1968) and 3-7% in the mouse retina (Sun et al 2002;Xu and Tian 2007). Here we show ON DSGCs was ϳ10% at P30 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…If the rate of RGC dendrite extension is different from interstitial stretch, rewiring is required to maintain the neural circuitries. Many studies in the literature examined the developmental changes of the RGCs including transient features, dendritic remodeling, stratification, and interaction in many species (Perry and Linden, 1982;Leventhal et al, 1988;Ramoa et al, 1988;Yamasaki and Ramoa, 1993;Weber et al, 1998;Wong et al, 2000;Wong and Wong, 2001;Yamagata et al, 2002;Lin et al, 2004;Mumm et al, 2005;Xu and Tian, 2007;Tian, 2008;Yamagata and Sanes, 2008). To our knowledge, the only attempt in the literature to evaluate differential change of the ganglion cell density is in the rabbit retina using Müller cells as a reference (Reichenbach et al, 1993;Deich et al, 1994).…”
Section: Introductionmentioning
confidence: 94%